2005
DOI: 10.1002/eji.200535401
|View full text |Cite
|
Sign up to set email alerts
|

Severe combined immunodeficiency and microcephaly in siblings with hypomorphic mutations in DNA ligase IV

Abstract: DNA double-strand breaks (dsb) during V(D)J recombination of T and B lymphocyte receptor genes are resolved by the non-homologous DNA end joining pathway (NHEJ) including at least six factors: Ku70, Ku80, DNA-PK cs , Artemis, Xrcc4, and DNA ligase IV (Lig4). Artemis and Lig4 are the only known V(D)J/NHEJ factors found deficient in human genetic disorders. Null mutations of the Artemis gene result in a complete absence of T and B lymphocytes and increased cellular sensitivity to ionizing radiations, causing rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(131 citation statements)
references
References 36 publications
2
127
1
1
Order By: Relevance
“…In vitro studies revealed no residual LIG4 adenylation or ligation activity in that combination of mutations (Girard et al, 2004). Two siblings who presented with SCID, growth defects and microcephaly were found to harbor compound heterozygous mutations conferring a Q280R substitution on one allele and a K424 frame-shift mutation that resulted in truncation of the C terminus on the other allele (Buck et al, 2006b). Identification of only hypomorphic mutations in LIG4 syndrome individuals suggests that loss of LIG4 would be incompatible with viability, as partially attenuated activity has a profound developmental defect.…”
Section: Defective Nhej Deficiency and Human Diseasementioning
confidence: 95%
“…In vitro studies revealed no residual LIG4 adenylation or ligation activity in that combination of mutations (Girard et al, 2004). Two siblings who presented with SCID, growth defects and microcephaly were found to harbor compound heterozygous mutations conferring a Q280R substitution on one allele and a K424 frame-shift mutation that resulted in truncation of the C terminus on the other allele (Buck et al, 2006b). Identification of only hypomorphic mutations in LIG4 syndrome individuals suggests that loss of LIG4 would be incompatible with viability, as partially attenuated activity has a profound developmental defect.…”
Section: Defective Nhej Deficiency and Human Diseasementioning
confidence: 95%
“…Several cases of B‐cell leukaemia and lymphoma were identified in patients with mutations in the ligase IV gene 67, 100. Moreover, murine models with hypomorphic ligase IV mutations develop thymic lymphoma, which further indicates the importance of ligase IV in the prevention of malignant transformation 101.…”
Section: Mechanisms Of Cancer Developmentmentioning
confidence: 99%
“…In most patients, this leads to severe ablation of T and B lymphocytes and cells derived from these patients have impaired V(D)J recombination. However, in some patients, ligase IV residual activity is sufficient for recombining TCRα and TCRβ regions 67. In summary, ligase IV deficiencies present with various phenotypes where the degree of immune deficiency and neurological defects is highly variable.…”
Section: Genes and Diseases Associated With Defective Recombination Imentioning
confidence: 99%
“…In contrast to RS-SCIDs, these patients are not completely devoid of B and T lymphocytes, although their numbers can be drastically reduced. Several other reports of DNA-LigaseIV deficiency further demonstrated the high heterogeneity of this syndrome for its impact on immunodeficiency (from no deficiency to SCID) as well as on its developmental consequences (with or without microcephaly) and cancer incidence (Ben-Omran et al, 2005;Enders et al, 2006;van der Burg et al, 2006;Buck et al, 2006b). In the more severe forms, the V(D)J recombination is strongly affected both quantitatively and qualitatively as a consequence of the DNA rejoining deficiency.…”
Section: Artemismentioning
confidence: 92%